Implementasi Web Service Pada Sistem Akuakultur Berbasis Internet of Things - Rahmawati, Rika; Nasir, Muhammad; Hidayat, Hari Toha; Amri, Amri; Ramadhani, Ayu (Politeknik Negeri Lhokseumawe, 2025)
Aquaculture is oriented towards a sustainable environment that requires more attention, fish can live and breed well if their environmental requirements have been met or are close to their natural habitat. The main parameter in carrying out fish farming is water quality. The main parameter in carrying out fish farming is water quality. Water quality needs to be monitored regularly so that success in aquaculture is achieved. API that functions to integrate between applications to facilitate communication between the two. The method used, namely rest web service, is expected to be used by IoT device developers and web application developers for monitoring and controlling freshwater fish farming. The results of the implementation of web services in an internet-based aquaculture system of things with this to make it easier to do. With this system, monitoring and control can also be done remotely (online) and in real time by cultivators. The results obtained from testing using jmeeter conducting load testing tests were obtained using virtual users and there were response times in milliseconds. Testing the response times based on the number of users, 250 users entered the 1.0 category with a description of some lags, but users are unlikely to see the disturbance and when entering thousands of users experience a long delay, which is more than a maximum waiting time of 10 seconds so that this causes users to experience interruptions due to the resulting waiting time with an error rate above 50.00%.